UPAYA MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS VII MELALUI PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) - Pertiwi, Yohana (Educatio Vitae, 2014)
achievement by using cooperating learning type Think Pair Share (TPS). The research that is used is Class Action Research that is held for about 2 cycles. The objective research is the students of VII (7th) grade of Junior High School 3 Madiun, in period 2012/2013 the total students is 33 students. Technique of  collecting data that is used is by using test method, observation method, and field note. Test method is used to know the data of the raising of mathematics study’s achievement, observation method is used to know the activity of student during the class, while field not is used to collect the data in the field. The results of the research are as follows the achiement of student’s mathematic’s study gets the average of cycle test I is 58,56 with the total prosentase of the class for about 50%, while cycle II with the average test for about 66,44 with prosentase of the class for about 59,38%. The total of average’s score of class activity, cycle I for about 3,12 and cycle II 3,39. The result of observation of student learning’s activity, the student of medium and high in the cycle I is 42,31% and cycle II is 63,31%.The result of student’s mathematics learning for the last test, all of the cycle reach the average for about 78,44 with the complete score of the student for about 65,63%. The total of student’s achiement, the process of class activity, and student’s activity from cycle I to cycle II gets raising.